Dual role for Drosophila epidermal growth factor receptor signaling in early wing disc development - Shu‐Huei Wang; Amanda Simcox; Gerard Campbell (2000)
Cell fate decisions in the early Drosophila wing disc assign cells to compartments (anterior or posterior and dorsal or ventral) and distinguish the future wing from the body wall (notum). Here we show that EGF-receptor (EGFR) signaling stimulated by its ligand, Vein, has a fundamental role in regulating two of these cell fate choices: (1) Vn/EGFR signaling directs cells to become notum by antagonizing wing development and by activating notum-specifying genes; (2) Vn/EGFR signaling directs cells to become part of the dorsal compartment by induction of apterous , the dorsal selector gene, and consequently also controls wing development, which depends on an interaction between dorsal and ventral cells.